Quasi-FM Waveform Using Chaotic Oscillator for Joint Radar and Communication Systems. (November 2021) - Pappu, Chandra S.; Carroll, Thomas L.
Highlights: A higher-dimensional chaotic oscillator is used for joint radar and communication systems. The chaotic system can be divided into two subsystems one with low-frequency and the other with varying frequency as a function of a low-frequency thereby generating quasi-FM waveforms. Digital information is encoded using chaos shift keying (CSK). Information was decoded using multiple fast self-synchronized chaotic receivers, and the bit error rates were close to the theoretical rate for frequency-shift keying. We showed that the decoding scheme is independent of timing errors and Doppler shifts. The communications signal could be used simultaneously as a radar signal, and the radar performance was characterized. The ambiguity function revealed a thumbtack shape that is required for high-resolution imagery of targets. Because of the noise-like properties of the modulated waveform, the proposed system could replace existing technologies such as noise generators and voltage-controlled oscillators (VCO) that are typically used at transmitter sites. The proposed communication technology can replace the existing communication receivers as they heavily rely on accuracy in clock synchronization. Abstract: The authors propose a novel signal design for generating wideband quasi-Frequency Modulated (FM) waveforms using chaotic systems. The receiver is based on a self synchronizing chaotic system, making for fast synchronization that is robust to timing errors or Doppler shifts. The chaotic oscillator has fast and slow time scales, and the slow oscillating part of the chaotic system is used to sweep the fast oscillating part thereby generating a modulated waveform that changes its frequency as a function of time. The potentials of these waveforms are demonstrated for joint radar-communication (RadComm) systems. Using the same nonlinear system a chaos frequency shift keying (CFSK) approach is utilized to encode the digital information. To decode the information, a drive-response synchronization scheme is utilized. Results indicate that our proposed signal design closely matches the bit-error rate (BER) of theoretical noncoherent frequency shift keying (FSK) while having good radar imaging capabilities.